Glass composition

The aluminosilicate glass composition, with its precise formulation and inclusion of specific oxides, addresses the challenge of achieving white light emission by stabilizing monovalent copper ions and optimizing the emission spectrum, resulting in a glass suitable for lighting applications.

JP2025050399APending Publication Date: 2025-04-04NAT UNIV KYOTO INST OF TECH
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2023159168
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-09-22
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

Conventional glass compositions struggle to emit white light effectively due to narrow emission spectra and issues with color rendering, particularly when excited by ultraviolet LEDs.

Method used

A specific aluminosilicate glass composition is developed, incorporating SiO2, Al2O3, B2O3, MgO, CaO, SrO, and ZrO2, with carefully controlled molar ratios and the inclusion of Cu2O and SnO2, which emits light at wavelengths above 300nm and exhibits a color difference value close to zero on the UV chromaticity diagram.

Benefits of technology

The glass composition achieves a light emitting color that is white or very close to white, suitable for lighting applications, by maintaining stability of monovalent copper ions and optimizing the emission spectrum to align with the blackbody radiation locus on the chromaticity diagram.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025050399000010
    Figure 2025050399000010
  • Figure 2025050399000011
    Figure 2025050399000011
  • Figure 2025050399000012
    Figure 2025050399000012
Patent Text Reader

Abstract

To provide a glass composition capable of exhibiting an emission color of white or very close to white.SOLUTION: The glass composition of the present invention contains the following components: (a) component; SiO2, (b) component; Al2O3, and (c) component; at least one selected from the group consisting of B2O3, MgO, CaO, SrO, and ZrO2, in specific content ratios, has the property of emitting light with a wavelength of 300 nm or more, and satisfies the following formula (I). -0.01≤duv≤0.01...(I) (In formula (I), duv represents the value of the color difference calculated based on the point on the uv chromaticity diagram of the emission spectrum obtained by irradiation with ultraviolet light at a wavelength of 365 nm and the black body radiation locus.)SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a glass composition. [Background technology]

[0002] From the viewpoint of promoting energy conservation, fluorescent lamps, which have been the mainstream for indoor lighting, are being rapidly replaced by white LEDs in recent years. A typical white LED combines a blue LED with an emission peak around 470 nm with a yellow-emitting phosphor, which creates light that appears white to the human eye. With this method, the light spectrum is not smooth in the visible light range and is significantly different from the spectrum of sunlight, which is most natural to the human eye, and the spectrum of blackbody radiation that is the basis of this spectrum. This leads to problems such as a lack of naturalness as lighting and poor reproducibility of the appearance of the color of an object, known as color rendering.

[0003] In order to solve such problems, methods of combining multiple phosphors with different emission wavelength ranges, methods of using ultraviolet LEDs to prevent the presence of sharp peaks of excitation light in the visible light range, or combinations of these methods have been devised. However, in the method of combining multiple phosphors with different emission wavelength ranges, different phosphor particles are in a relationship of shielding each other's excitation light, which causes a problem of reduced luminous efficiency. In addition, if there is an overlap between the excitation wavelength range and the emission wavelength range of each phosphor, cascade excitation occurs in which the light emitted from one phosphor causes the other phosphor to emit light, which can cause problems such as variation in the emission color between products and expansion of chromatic aberration in the irradiation area. Even in the method of using ultraviolet LEDs, there is no phosphor with a wide band of emission that covers the entire visible range with a single phosphor, and the above problems occur when multiple phosphors are used.

[0004] From this viewpoint, various kinds of phosphors that are excited by ultraviolet light and emit light in a wide band in the visible range have been researched. For example, Non-Patent Document 1 reports an aluminosilicate oxyfluoride glass that emits light when exposed to ultraviolet light with a wavelength of 290 to 338 nm due to monovalent copper ions. Non-Patent Document 2 reports a Cu 2 O and SnO2 It has been reported that alkali borosilicate glasses doped with Cr and Ni emit light upon exposure to ultraviolet light.

[0005] Patent Document 1 describes a crystal-free glass that emits fluorescence in the range of 380 to 750 nm when excited by light with a wavelength of 240 to 405 nm, and is made of SnO x (x=1-2, but typically x=1 or 2), P 2 O 5 , ZnO, MnO y (y=1 to 2, but typically y=1 or 2) is disclosed. 2 50-85%, Al 2 O 3 1 to 15%, Li 2 O, Na 2 O or K 2 O, 7-30% in total, MgO or CaO, 0-18% in total, Cu 2 Contains 0.1-1% O and 0.2-5% SnO. 2 Molar ratio of SnO / Cu 2 Luminescent glasses in which O is 1-10 are disclosed.

[0006] In Patent Document 3, at least B is used as a glass-forming oxide. 2 O 3 It is described that a luminescent glass having a host glass containing MO (M represents a Group 2 element) emits yellow light at an excitation wavelength of 360 nm. [Prior art documents] [Patent documents]

[0007] [Patent Document 1] International Publication No. WO2012-063492 [Patent Document 2] JP 2016-79045 A [Patent Document 3] JP 2014-133682 A [Non-patent literature]

[0008] [Non-Patent Document 1] Y. Shi, R. Weil, J. Guo, X. Tian, ​​F. Hu and H. Guo, “Influence of Optical Basicity on Cu+ Luminescence in Aluminosilicate Oxyfluoride Glasses”, Front. Mater., 6 (2019) 246. [Non-Patent Document 2] Yasumori et al., Proceedings of the 50th Glass and Photonics Materials Symposium, 1B06 (2009) p23. Summary of the Invention [Problem to be solved by the invention]

[0009] However, the glass disclosed in Non-Patent Document 1 has an emission color that is far from the white point (0.333, 0.333) on the xy chromaticity diagram, ranging from yellow-green to yellow, and is difficult to call white. The reason for this is that the emission spectrum is not broad enough, and the emission is weak on both the short-wavelength side and the long-wavelength side of the visible light range. The glass disclosed in Non-Patent Document 2 has a weak emission on the short-wavelength side of the visible light range of the emission spectrum, and the emission color is yellow, not white.

[0010] The glass disclosed in Patent Document 1 mainly utilizes the emission of divalent Sn ions, so it is considered that the emission is weak at an excitation wavelength of 300 nm or more, and the excitation wavelength in the examples shown is limited to 254 to 287 nm, and practical emission cannot be obtained, particularly when excited by ultraviolet LEDs with a high output and easily available emission wavelength of around 365 nm, which is inconvenient. Patent Document 2 only describes the emission efficiency of the luminescent glass at an excitation wavelength of 360 nm, but does not consider the emission color at all, and it is considered that white light has not been obtained. The glass disclosed in Patent Document 3 emits yellow light, and cannot produce white light close to the white point on the chromaticity diagram.

[0011] As described above, it is difficult to emit white light with conventional glasses, and there is still room for improvement in terms of providing light suitable for illumination.

[0012] The present invention has been made in view of the above, and has an object to provide a glass composition capable of emitting white light or a light color very close to white. [Means for solving the problem]

[0013] The inventors have reported that the copper ion-doped glass is characterized by the presence of univalent copper ions, Cu + As a result of extensive research into a composition in which only one aluminosilicate glass is present and which provides a wide-band emission spectrum when irradiated with ultraviolet light at around 365 nm, it was discovered that, as will be described later, in a specific composition range of aluminosilicate glass, emission that is extremely close to the blackbody radiation locus on a chromaticity diagram, in particular its white region, can be obtained, which has led to the completion of the present invention.

[0014] That is, the present invention includes, for example, the subject matter described in the following sections. Item 1 The following components (a), (b) and (c) (a) Component: SiO 2 (b) Component; Al 2 O 3 ,and (c) Component; B 2 O 3 , MgO, CaO, SrO and ZrO 2 A component containing at least one selected from the group consisting of Including, Relative to the total amount of the component (a), the component (b) and the component (c), SiO 2 The content is 60 to 73 mol%, Al 2 O 3 The content is 10 to 20 mol%, B 2 O 3 The content is 15 mol% or less, The content of MgO is 20 mol% or less. The CaO content is 20 mol% or less. The content of SrO is 8 mol% or less. ZrO 2 The content is 2 mol% or less, and The total content of MgO, CaO and SrO is 12 to 25 mol%. and Al 2 O 3 and SiO 2 Al relative to the total amount 2 O 3 Molar ratio of (Al 2 O 3 / (Al 2 O 3 +SiO 2 ) is between 0.13 and 0.23, R'O and Al 2 O 3 The molar ratio of R'O to the total amount of (R'O / (R'O+Al 2 O 3 ) value, where R'O represents MgO, CaO and SrO) is 0.40 to 0.65, The component (a), the component (b), the component (c), Cu 2 O and SnO 2 Cu 2 The content of O is 0.1 to 3 mol % and SnO 2 The content of is 1 mol % or less, Cu 2 SnO vs. O 2 Molar ratio of SnO 2 / Cu 2 O value) is 2.5 or less, It has the property of emitting light at wavelengths of 300 nm or more. The following formula (I) -0.01≦d uv ≦0.01 (I) (In formula (I), d uv represents the color difference value calculated based on the point on the UV chromaticity diagram of the emission spectrum obtained by irradiating ultraviolet light with a wavelength of 365 nm and the blackbody radiation locus. A glass composition comprising: Section 2 Relative to the total amount of the component (a), the component (b) and the component (c), SiO 2 The content is 62 to 73 mol%, Al 2 O 3 The content is 13 to 19 mol%, B 2 O 3 The content is 1 mol% or less, The content of MgO is 11 to 19 mol%, The CaO content is 6 mol% or less. The content of SrO is 5 mol% or less. and, The total content of MgO, CaO and SrO is 13-19 mol%. and The above Al 2 O 3 / (Al 2 O 3 +SiO 2 ) is between 0.155 and 0.23, the molar ratio of MgO to R'O (MgO / R'O value) is 0.40 to 1; The above R´O / (R´O+Al 2 O 3 2. The glass composition according to item 1, wherein the value of (a) is 0.40 to 0.55. Section 3 The following formula (II) -0.005≦d uv ≦0.005 (II) (In formula (II), d uv is d in the formula (I) uv (Synonymous with Item 3. The glass composition according to item 1 or 2, which satisfies the above. Effect of the Invention

[0015] The glass composition according to the present invention is capable of emitting white light or a color very close to white. [Brief description of the drawings]

[0016] [Figure 1]1 shows XRD patterns of the glass composition obtained in Example 3 and the glass composition obtained in Example 7. [Diagram 2] 1 shows the results of measuring the emission spectra of the glass compositions obtained in Examples 1, 2, 3 and 14. [Diagram 3] 1 shows the results of waveform separation of the emission spectrum of the glass composition obtained in Example 3. [Figure 4] The chromaticity coordinates (Examples 1, 2, 3, 5, 6, 11, 12, 25, and 27) in the xy chromaticity diagram are shown, along with the blackbody locus and the chromaticity coordinates of the white point. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0017] Hereinafter, embodiments of the present invention will be described in detail. In this specification, the expressions "containing" and "comprise" include the concepts of "containing", "comprises", "consists essentially of" and "consists only of".

[0018] In the numerical ranges described in stages in this specification, the upper or lower limit of a certain numerical range can be arbitrarily combined with the upper or lower limit of another numerical range. In the numerical ranges described in this specification, the upper or lower limit of the numerical range may be replaced with a value shown in an example or a value that can be unambiguously derived from an example. In addition, in this specification, a numerical value connected with "~" means a numerical range that includes the numerical values ​​before and after "~" as the lower and upper limits.

[0019] The glass composition of the present invention comprises the following components (a), (b) and (c): (a) Component: SiO 2 (b) Component; Al 2 O 3 , and (c) Component; B 2 O 3 , MgO, CaO, SrO and ZrO 2 A component containing at least one selected from the group consisting of Includes.

[0020] The glass composition of the present invention contains, relative to the total amount of the component (a), the component (b) and the component (c), SiO 2 The content is 60 to 73 mol %, Al 2 O 3 The content is 10 to 20 mol %, B 2 O 3 The content ratio of is 15 mol % or less, The content of MgO is 20 mol% or less, The CaO content is 20 mol% or less, The content of SrO is 8 mol% or less, ZrO 2 The content ratio of is 2 mol% or less, and The total content of MgO, CaO and SrO is 12 to 25 mol %.

[0021] The glass composition of the present invention is Al 2 O 3 and SiO 2 Al relative to the total amount 2 O 3 Molar ratio of (Al 2 O 3 / (Al 2 O 3 +SiO 2 ) is 0.13 to 0.23, and R'O and SiO 2 The molar ratio of R'O to the total amount of (R'O / (R'O+Al 2 O 3 ) where R'O represents MgO, CaO and SrO) is 0.40 to 0.65.

[0022] The glass composition of the present invention comprises the component (a), the component (b), the component (c), Cu 2 O and SnO 2 Cu 2 The content of O is 0.1 to 3 mol % and SnO 2 The content of Cu is 1 mol% or less. 2 SnO vs. O 2 Molar ratio of SnO2 / Cu 2 O value) is 2.5 or less.

[0023] The glass composition of the present invention has a property of emitting light at a wavelength of 300 nm or more, The following formula (I) -0.01 <d uv <0.01 (I) (In formula (I), d uv represents the color difference value calculated based on the point on the UV chromaticity diagram of the emission spectrum obtained by irradiating ultraviolet light with a wavelength of 365 nm and the blackbody radiation locus. Meet the following.

[0024] The glass composition of the present invention can emit light of white or a color very close to white. Therefore, by using the glass composition of the present invention, it is possible to produce glass that emits light of a color whose chromaticity coordinates are close to the blackbody radiation locus on a chromaticity diagram, and the glass is suitable for lighting applications that provide suitable light.

[0025] (a) Ingredients The component (a) contained in the glass composition of the present invention is SiO 2 SiO 2 is an essential component that constitutes the network structure of glass. In the glass composition of the present invention, SiO 2 is a component necessary to reduce the basicity of the entire glass and to suppress the phenomenon in which copper ions receive electrons and are reduced to metal. The stable presence of monovalent copper ions in glass is a necessary condition for the glass's good luminescence properties.

[0026] The glass composition of the present invention is SiO 2 (i.e., component (a)) is contained in an amount of 60 to 73 mol % (i.e., 60 mol % or more and 73 mol % or less) based on the total amount of components (a), (b), and (c) (hereinafter referred to as "total amount S"). 2 If the content of SiO is less than 60 mol %, the stability of the glass network structure may decrease and the devitrification temperature may increase. 2If the content of SiO exceeds 73 mol%, melting becomes difficult, and it becomes difficult to obtain the desired glass. 2 The content is preferably 62 mol% or more, more preferably 63 mol% or more, and even more preferably 65 mol% or more, and is preferably 73 mol% or less, and more preferably 72 mol% or less.

[0027] (b) Component The component (b) contained in the glass composition of the present invention is Al. 2 O 3 The glass composition of the present invention is SiO 2 Together with Al 2 O 3 By containing Al, monovalent copper ions are stably held. 3+ Since they exist in the form of ions, if there are monovalent metal ions (Me + When the oxygen ion is four-coordinated AlO 4- and Me + Therefore, when copper ions, which are monovalent metal ions, are present in the glass, the copper ions can be stably maintained in a monovalent state.

[0028] The glass composition of the present invention is Al 2 O 3 (i.e., component (b)) is contained in an amount of 10 to 20 mol % (i.e., 10 mol % or more and 20 mol % or less) based on the total amount of S. 2 If the content of Al is less than 10 mol %, the effect of stabilizing the monovalent copper ions becomes small, and if it exceeds 20 mol %, the viscosity and devitrification temperature increase, and the melting property deteriorates, making it difficult to obtain the desired glass. 2 O 3 The content is preferably 13 mol% or more, more preferably 14 mol% or more, and even more preferably 15 mol% or more, and is preferably 19 mol% or less, and more preferably 18 mol% or less.

[0029] The glass composition of the present invention is Al 2 O 3 and SiO 2 Al relative to the total amount 2 O 3 (i.e., Al 2 O 3 Moles of Al / (Al 2 O 3 +SiO 2 The molar ratio of Al to copper (molar value) is 0.13 to 0.23 (i.e., 0.13 or more and 0.23 or less). If the molar ratio is less than 0.13, the effect of stabilizing monovalent copper ions becomes small, and if it exceeds 0.23, the devitrification temperature rises and meltability deteriorates, making it difficult to obtain the desired glass. 2 O 3 and SiO 2 Al relative to the total amount 2 O 3 The molar ratio is preferably 0.14 or more, more preferably 0.155 or more, even more preferably 0.16 or more, and particularly preferably 0.17 or more, and is preferably 0.3 or less, more preferably 0.25 or less, and even more preferably 0.22 or less.

[0030] (c) Component The component (c) contained in the glass composition of the present invention is B 2 O 3 , MgO, CaO, SrO and ZrO 2 It is a component containing at least one selected from the group consisting of:

[0031] (c) Among the components, B 2 O 3 B is a component that can easily suppress an increase in viscosity even at high temperatures, can further improve the melting property of glass, and can also bring about the effect of stably retaining monovalent copper ions. 2 O 3 If the content is too high, the emission spectrum becomes narrow and the emission color tends to be green or yellow. 2 O 3The content of B relative to the total amount S must be 15 mol % or less, preferably 12 mol % or less, more preferably 8 mol % or less, further preferably 5 mol % or less, and particularly preferably 1 mol % or less. 2 O 3 The content of may be 0 mol % (i.e., B 2 O 3 (It does not have to include ).

[0032] Among the (c) components, MgO can improve the meltability of glass, and among divalent ions, it has a small effect of increasing the basicity of glass, and is easy to maintain the state in which monovalent copper ions are stably held in the aluminosilicate glass, so it is a component that can further promote vitrification. However, if the content of MgO is too high, the devitrification temperature of the glass may increase, so the content of MgO must be 20 mol% or less with respect to the total amount of S, preferably 19 mol% or less, and more preferably 18 mol% or less. The content of MgO with respect to the total amount of S may be 0 mol% (i.e., no MgO is included), and is preferably 11 mol% or more, more preferably 13 mol% or more, and particularly preferably 15 mol% or more.

[0033] Of the components (c), CaO is a component that can easily suppress an increase in viscosity even at high temperatures and can further improve the meltability of glass. However, if the CaO content is too high, the basicity of the glass increases, the ability of the glass to retain monovalent copper ions decreases, and the glass may become more susceptible to devitrification, so the CaO content must be 20 mol% or less relative to the total amount of S, preferably 10 mol% or less, more preferably 8 mol% or less, and particularly preferably 6 mol% or less. The CaO content relative to the total amount of S may be 0 mol% (i.e., CaO may not be included).

[0034] Among the components (c), SrO is a component that can easily suppress an increase in viscosity even at high temperatures, can further improve the melting property of the glass, and can make the glass more stable and less susceptible to devitrification by combining with MgO and CaO. However, if the content of SrO is too high, the basicity of the glass increases and the ability of the glass to retain monovalent copper ions may decrease, so the content of SrO must be 8 mol % or less relative to the total amount of S, preferably 5 mol % or less, and more preferably 1 mol % or less. The content of SrO relative to the total amount of S may be 0 mol % (i.e., SrO may not be included).

[0035] (c) Among the components, ZrO 2 is a component that can improve devitrification and does not significantly affect the luminescence characteristics. 2 The content of ZrO relative to the total amount of S must be 2 mol % or less, and preferably 1 mol % or less. 2 The content of may be 0 mol % (i.e., ZrO 2 (It does not have to include ).

[0036] (c) Component is B 2 O 3 It is preferable that the oxide is at least one selected from the group consisting of MgO, CaO and SrO.

[0037] In the glass composition of the present invention, the total content of MgO, CaO and SrO is 12 to 25 mol% (i.e., 12 mol% or more and 25 mol% or less) relative to the total amount of S. If the total content of MgO, CaO and SrO relative to the total amount of S is less than 12 mol%, the meltability of the glass may be insufficient, and if it exceeds 25 mol%, the glass may be easily devitrified and the basicity of the glass may increase, resulting in a decrease in the ability to retain monovalent copper ions. The total content of MgO, CaO and SrO is preferably 13 mol% or more relative to the total amount of S, and is preferably 19 mol% or less.

[0038] Here, when MgO, CaO and SrO are expressed as R'O, the glass composition of the present invention is R'O and Al 2 O 3 The molar ratio of R'O to the total amount of (i.e., the number of moles of R'O / (R'O+Al 2 O 3 The value of the number of moles of R'O and Al is 0.40 to 0.65 (i.e., 0.40 or more and 0.65 or less). 2 O 3 If the molar ratio of R'O to the total amount of Al is less than 0.40, the viscosity of the glass at high temperatures may become high, and if it exceeds 0.65, the effect of stably retaining monovalent copper ions may become small, and the devitrification temperature may also increase. 2 O 3 The molar ratio of R'O to the total amount of is more preferably 0.55 or less.

[0039] In addition, the glass composition of the present invention preferably has a molar ratio of MgO to the R'O (i.e., the value of the number of moles of MgO / the number of moles of R'O) of 0.40 to 1 (i.e., 0.40 or more and 1 or less). In this case, a glass that is less susceptible to devitrification is easily obtained, and the ability of the glass to retain monovalent copper ions is easily improved. The molar ratio of MgO to the R'O is preferably 0.5 or more, and more preferably 0.7 or more.

[0040] Cu 2 O The glass composition of the present invention further comprises, in addition to the component (a), the component (b) and the component (c), Cu. 2 Contains O.

[0041] Cu 2 O is a monovalent copper ion (Cu + ) into glass. Normally, copper is introduced as a divalent ion (Cu 2+ ), monovalent ions (Cu + ) and metallic state (Cu 0, often in a colloidal state), they are known to color glass blue, colorless, and red (in the case of a colloid), respectively. Among them, it is monovalent copper ions (Cu + The glass composition of the present invention contains the above-mentioned component (a), component (b) and component (c) in a specific ratio, and converts copper present in the glass into monovalent copper ions (Cu + ) state.

[0042] In the present invention, copper oxide is referred to as Cu 2 In the present invention, the glass is represented as monovalent copper ions (Cu + The purpose of the glass is to have only cuprous oxide (CuO) present, so this is in line with the above. 2 In addition to copper oxide (CuO), copper oxide (CuO) may also be used. When copper oxide is used as the raw material, a larger amount of reducing agent is required than when copper oxide is used, but it can be used without any problems.

[0043] In the glass composition of the present invention, Cu 2 The content ratio of O is the same as that of the (a) component, the (b) component, the (c) component, Cu 2 O and SnO 2 The amount of Cu is 0.1 to 3 mol % (i.e., 0.1 mol % or more and 3 mol % or less) relative to the total amount of Cu. 2 If the O content is less than 0.1 mol %, the luminescence may be weak. 2 If the O content exceeds 3 mol %, the emission spectrum of the glass is biased toward the long wavelength side, making it difficult to obtain white light. 2 The O content is preferably 0.2 mol % or more, more preferably 0.4 mol % or more, and is preferably 2.5 mol % or less.

[0044] Other Ingredients The glass composition of the present invention may contain other components as necessary. For example, SnO 2 Examples include:

[0045] SnO 2 As has long been known as a technique for producing copper red glass, by using carbon or other reducing agents, the copper ions in the glass are converted to Cu. + The glass composition of the present invention acts as an effective reducing agent to convert SnO 2 If it contains SnO 2 The content ratio of the (a) component, the (b) component, the (c) component, Cu 2 O and SnO 2 The amount of SnO is 1 mol % or less. 2 If the content of SnO exceeds 1 mol %, the emission spectrum is biased toward the long wavelength side, and the emission color deviates from white. 2 The content of is preferably 0.6 mol % or less, more preferably 0.1 mol % or less, and may be 0 mol % (i.e., SnO 2 (It does not have to include ).

[0046] In the glass composition of the present invention, Cu 2 SnO vs. O 2 (i.e., SnO 2 moles / Cu 2 The moles of CuO are less than 2.5. 2 SnO vs. O 2 When the molar ratio of Cu exceeds 2.5, the emission spectrum is biased toward the long wavelength side, and the emission color deviates from white. 2 SnO vs. O 2 The molar ratio of Cu is preferably 2.2 or less, more preferably 1 or less, further preferably 0.5 or less, and particularly preferably 0.1 or less. 2 SnO vs. O 2 The molar ratio of may be 0.

[0047] The glass composition of the present invention comprises Li 2 O, Na 2 O and K 2 The amount of O can be 0.1 mol % or less relative to the total amount of S, and it is more preferable that the amount of O is substantially zero. 2 O, Na2 O and K 2 O is a component that promotes the melting of glass, but if it is substantially not contained, the emission spectrum is less likely to be biased toward the long wavelength side, and the emission color is less likely to deviate from white.

[0048] In this specification, the term "substantially free" means that the influence of the undesirable action caused by the addition of the component described above is negligible, and does not exclude, for example, the inclusion of the component to the extent that devitrification is improved, or the unavoidable inclusion of the component.

[0049] P 2 O 5 is a component that promotes the melting of glass, but since the emission spectrum is biased toward the long wavelength side and the emission color deviates from white, it is preferable that it is substantially not contained.

[0050] F is a component that promotes the melting of the raw materials, but since the emission spectrum is biased toward the long wavelength side and the emission color deviates from white, it is preferable that it is substantially not contained.

[0051] Of the alkaline earth oxides, BaO has a large effect of increasing the basicity of the glass and a small effect of stably retaining monovalent copper ions, and therefore it is preferable that BaO is not substantially contained.

[0052] Glass composition The glass composition of the present invention may contain components other than metal oxides as long as the effects of the present invention are not impaired. The glass composition of the present invention preferably contains the (a) component, the (b) component, and the (c) component in a total mass of 80 mass% or more, more preferably 90 mass% or more, even more preferably 95 mass% or more, and is preferably 99 mass% or less.

[0053] The glass composition of the present invention has the property of emitting light at a wavelength of 300 nm or more. The glass composition of the present invention preferably has the property of emitting light at a wavelength of 300 to 420 nm, and more preferably has the property of emitting light at a wavelength of 315 to 395 nm.

[0054] The glass composition of the present invention has the following characteristics: a color difference d obtained by comparing the point on the UV chromaticity diagram of the emission spectrum by irradiating ultraviolet light at 365 nm with the blackbody radiation locus uv -0.01≦d uv It is preferable that the range is -0.005≦d≦0.01. More preferable is -0.005≦d uv ≦0.005.

[0055] The shape of the glass composition of the present invention is not particularly limited and may be an appropriate shape depending on the application, for example, a lump, powder, plate, film, or the like.

[0056] The method for producing the glass composition of the present invention is not particularly limited, and for example, a method similar to a known method for producing a glass composition can be widely adopted. For example, the glass composition of the present invention can be obtained by mixing glass materials that are glass raw materials for the glass composition of the present invention, and then melting the resulting mixture.

[0057] The type of glass raw material is not particularly limited, and for example, a wide variety of known raw materials capable of forming the components (a), (b), and (c) can be used in the present invention, including oxides, carbonates, hydroxides, composite oxides, and the like of various metals.

[0058] Specific examples of glass raw materials are as follows. Raw materials for forming component (a) are various silicon oxides (SiO 2 The raw material for forming the component (b) is alumina (Al 2 O 3 (c) Among the components, B 2 O 3 The raw material for forming is boric anhydride (B 2 O 3Among the components (c), the raw material for forming MgO is magnesium oxide (MgO). Among the components (c), the raw material for forming CaO is calcium carbonate (CaCO 3 Among the components (c), the raw material for forming SrO is strontium carbonate (SrCO 3 (c) Among the components, ZrO 2 The raw material for forming zirconium oxide (ZrO 2 The glass raw materials include raw materials for forming the (a) component, Cu, 2 Contains O.

[0059] The glass raw material preferably contains a reducing agent. The type of reducing agent is not particularly limited, and for example, a wide variety of known reducing agents can be used, specifically, carbon, etc. When the glass raw material contains a reducing agent, the copper ions in the glass become monovalent Cu + This makes it easier for the information to be retained.

[0060] It is preferable that the glass raw material does not contain sulfates. When sulfates of alkali metals or alkaline earth metals, which are generally used as fining agents, are used in melting the glass composition of the present invention, monovalent copper ions Cu + It is preferable not to add these sulfates because copper sulfide is generated and the glass may turn black under the reducing melting conditions used to obtain the glass. Examples of sulfates include sodium sulfate, gypsum (calcium sulfate), magnesium sulfate, and hydrates of these.

[0061] The method of melting the glass raw material can be widely adopted from known methods as long as the glass composition of the present invention can be sufficiently melted and the reducing property required to keep copper ions in a monovalent state can be maintained. For example, the glass raw material can be melted by heating the glass raw material in a crucible with an electric furnace. The glass composition of the present invention is an aluminosilicate type, and the melting temperature is preferably 1550°C or higher, more preferably 1580°C or higher, and particularly preferably 1600°C or higher. The molten glass obtained by melting the glass raw material can also be formed into a predetermined shape by an appropriate method.

[0062] Various gases can be used to make the melting atmosphere reducing or inert. The oxygen partial pressure p at which copper ions exist almost exclusively in monovalent form in the glass is O2 Although it depends on the glass composition, [Non-Patent Document 3] 1) W. D. Johnston and A. Chelko, “Oxidation-Reduction Equilibria in Molten Na 2 O 2SiO 2 Glass in Contact with Metallic Copper and Silver”, J. Am. Ceram. Soc., 49

[10] (1966)562-564. Based on this, 10 -9 For example, CO (carbon monoxide) and CO 2 The ratio of partial pressures of the two gases (carbon dioxide) p CO / p CO2 When a mixed gas with 1 / 10 oxygen is introduced into a furnace at 1600°C, calculations using thermodynamic data show that the oxygen partial pressure in the furnace is about 10 -9 This is a favorable state for making the copper ions in the glass almost monovalent. 2 (hydrogen) and H 2 In the case of a mixture of O (water vapor), the partial pressure ratio p H2 / p H2O When the oxygen partial pressure in the furnace at 1600°C is set to 3, the calculation using thermodynamic data shows that the oxygen partial pressure is about 10 -9In addition, inert argon gas is a standard product of G3 grade (purity > 99.999% by volume) and contains no impurities such as O 2 The oxygen concentration is less than 0.2 ppm by volume, and this oxygen concentration is converted to oxygen partial pressure of 10 -7 Therefore, when G3 grade argon gas is introduced into a furnace at 1600°C to melt the glass, the amount of reducing agent required to convert copper ions to monovalent copper is small, and it is easier to obtain copper ions in a monovalent state than when melting in air. 2 Mixed gas, H 2 -H 2 For the CO-CO mixed gas, argon gas was also added. 2 -Ar mixed gas, H 2 -H 2 It can also be used with O-Ar mixed gas.

[0063] As a melting method, glass raw materials can be heated in a crucible in an electric furnace, and glass particles can be obtained by passing granulated glass raw materials through a high-temperature gas flame. For example, a combustion flame of a hydrocarbon gas (methane, acetylene, etc.)-air or oxygen, or hydrogen-oxygen can be used. When these gases are burned, the ratio of the combustion gas to air or oxygen can be adjusted to make the combustion state slightly reducing, so that copper ions are present almost exclusively in monovalent form. A melting method called a containerless melting method or a levitation melting method can also be used. In this method, gas is blown from below onto the molten glass to melt it while it is suspended in the air. Heating can be performed by directly irradiating the glass sample with a laser beam, by heating with a heating element as in a normal electric furnace, or by using combustion gas. If the gas for levitating the glass is one with a controlled oxygen partial pressure as described above, it is effective for making the copper ions monovalent.

[0064] In specifying the invention included in the present disclosure, the configurations (properties, structures, functions, etc.) described in each embodiment of the present disclosure may be combined in any manner. In other words, the present disclosure includes all subject matter consisting of all combinations of the configurations that can be combined as described in this specification. EXAMPLES

[0065] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to the embodiments of these examples.

[0066] (Examples 1 to 10) Silicon oxide (SiO 2 ), boric anhydride (B 2 O 3 ), Alumina (Al 2 O 3 ), magnesium oxide (MgO), calcium carbonate (CaCO 3 ), strontium carbonate (SrCO 3 ), Cuprous oxide (Cu 2 O), stannic oxide (SnO 2 ) and zirconium oxide (ZrO 2 ) were selected and blended in predetermined amounts to prepare glass raw materials. Carbon was blended as a reducing agent into each glass raw material in the amounts shown in Table 1. In Table 1, the blended amount of carbon is shown as a relative value based on Example 3. The glass raw materials were blended so that the total mass of the resulting glass was 15 g. The composition in Table 1 does not include Cu, an added component. 2 O, SnO 2 The components other than (a), (b), and (c) are taken as the mother glass composition, which is expressed as 100 mol%. Therefore, Cu is added as an additive component. 2 O x mol%, SnO 2 When expressed as y mol%, this means that the mother glass is (100-xy) mol%.

[0067] The glass raw material was placed in an alumina crucible (Nikkato, SSA-H, B1), covered with an alumina lid (Nikkato, SSA-H, for B1 crucible) in the upside-down direction, and then placed in an alumina crucible (Nikkato, SSA-H, B3), covered with an alumina lid (Nikkato, SSA-H, for B4 crucible), and placed in an electric furnace. This setup was intended to minimize the burning of carbon added as a reducing agent by oxygen in the air. The electric furnace was heated from room temperature to 1600°C at a rate of 10°C / min, held at 1600°C for 1 hour, and then cooled to 25°C in 30 minutes using a program setting, and then allowed to cool to room temperature.

[0068] The output of the furnace became zero about 3 minutes after the start of the temperature drop, and the average cooling rate during that time was 50°C / min or more. The glass composition was recovered from the crucible after cooling. For glass compositions that had been in contact with the alumina crucible and near the crucible wall at the time of recovery and had become partially devitrified, these parts and, in some samples, the surface part of the molten glass that had been oxidized and turned blue were removed to obtain only the colorless glass part. In order to obtain the colorless glass part, the glass was melted and adjusted multiple times with the same composition but with different amounts of carbon added.

[0069] (Examples 11 to 20) A glass composition was obtained in the same manner as in Example 1, except that the glass composition ratio was changed as shown in Table 2.

[0070] (Examples 21 to 29) A glass composition was obtained in the same manner as in Example 1, except that the glass composition ratio was changed to that shown in Table 3.

[0071] (Evaluation method and results) The optical basicity is described in the following Non-Patent Document 4. Non-Patent Document 4; JA Duffy, “Basicity of Glass-Forming Melts”, in “Electrochemistry of Glasses and Glass Melts, Including Glass Electrodes”, H. Bach, FGK Baucke and D. Krause Eds., Springer-Verlag, Berlin, 2000, pp 275-301. The composition was calculated from the mother glass composition based on the method described in .

[0072] The colorless glass pieces obtained in each of the Examples and Comparative Examples were irradiated with a 365 nm ultraviolet LED (OSV1XDE5E1S manufactured by OptoSupply, rated input 5 W) at an input power of 3.7 W (voltage 4.0 V, current 0.93 A). The light emitted from the glass pieces at this time was visually observed, and the visually recognized light emission color is shown in the table below.

[0073] The colorless glass pieces obtained in each example were crushed in an agate mortar to obtain glass powder. The X-ray diffraction (XRD) pattern of this glass powder was measured at a diffraction angle (2θ) range of 10 to 70° using an X-ray diffraction measuring device Mini Flex-600 manufactured by Rigaku. If the obtained XRD pattern only had a gentle glass halo, it was judged to be completely vitrified, and if it had a steep peak thought to be due to crystallization, it was judged to be partially crystallized. ○: Only a glass halo was observed, and it was determined that the glass was completely vitrified. Δ: Peaks thought to be due to crystals were observed, and it was determined that some crystallization had occurred.

[0074] The results of the determination are shown in Tables 1 to 3. In addition, the XRD patterns of Example 3, which was determined to be completely vitrified, and Example 7, which was determined to have a peak due to some crystals, are shown in FIG. 1. Among the samples in which a peak believed to be due to crystals was observed, Example 7 had the largest peak, and the glass halo and two peaks believed to be due to crystals were waveform separated by optimization using a pseudo-Voigt function, and the crystallization rate was calculated from the result, which was a very small value of about 0.25%. From this, it is estimated that even in samples in which a peak believed to be due to crystals was observed, the luminescence characteristics are almost determined by the glass. Based on this recognition, in the present invention, samples that are determined to contain a very small amount of crystals from the XRD measurement results as described above are also called "glass".

[0075] The glass powder was placed in a powder cell, and the emission spectrum was measured in the range of 380 to 700 nm with 365 nm excitation using a JASCO FP-6500 spectrofluorophotometer. During measurement, a filter glass that absorbs 390 nm or less was inserted on the detector side so that the excitation light would not enter the detector side. Examples of the measurement results of the emission spectrum of Examples 1, 2, 3, and 14 are shown in Figure 2. Note that the emission spectrum shown in Figure 2 shows the measurement data obtained under the same measurement conditions as it is, but the intensity ratio between different glasses is not necessarily correctly represented due to differences in the state of the powder, etc. Based on the measured emission spectrum, the following analysis was performed. The emission spectrum was waveform-separated into three emission bands with peaks near 400, 460, and 600 nm. The waveform separation was performed by converting the wavelength (nm) to photon energy (eV) and assuming that the spectrum of each emission band (i = 1, 2, 3 from the one with the largest photon energy) follows a Gaussian distribution expressed by the following formula (a).

[0076]

number

[0077] In formula (a), x is the photon energy (eV), f i (x) is the emission intensity at photon energy x (eV) in emission band i, Ai is the relative intensity of emission band i, μ i is the emission peak position of emission band i (eV), σ i is the standard deviation of the distribution of emission band i (eV), and f i The integral of (x) over the range of x is A i The overall spectrum is expressed as the sum of the intensities of the three waveform-separated emission bands, as shown in the following equation (b).

[0078]

number

[0079] Waveform separation is performed by calculating the square of the difference between the sum of the emission intensities of the three emission bands f(x) and the intensity of the measured emission spectrum g(x) at each photon energy point, and then adjusting A so that the sum over the entire range, i.e., the value of the following equation (c), is minimized. i , μ i , σ i This was done by optimizing the following:

[0080]

number

[0081] From the obtained results, the integral intensity of f(x) over the entire photon energy range is set to 1, that is, A is set to the following equation (d): i was standardized.

[0082]

number

[0083] A obtained as a result of waveform separation i , μ i , σ i are shown in Tables 1 to 3. As an example, the results of waveform separation of the emission spectrum of the glass of Example 3 are shown in FIG.

[0084] Next, the xy chromaticity coordinates of the emission spectrum of each glass were calculated based on CIE1931, and the uv chromaticity coordinates were calculated based on CIE1960 from the CIE1931 tristimulus values ​​XYZ, and the correlated color temperature T was calculated by comparing it with the blackbody radiation locus on the uv chromaticity diagram. CP , and color difference d UV was calculated. In this calculation, an approximation formula based on a Gaussian function was used as the CIE color matching function. For the range of 700-780 nm, where there was no measurement data for the emission spectrum, an interpolation was performed using the approximation formula obtained in the waveform separation described above. The blackbody radiation locus on the chromaticity diagram was calculated assuming that the spectral radiance of blackbody radiation is expressed by the following formula (e) in accordance with Planck's law.

[0085]

number

[0086] Here, B(λ, T) is the spectral radiance (J s) of blackbody radiation per unit surface area, unit solid angle, wavelength λ (m), and absolute temperature T (K). -1 m -2 ·sr -1 m -1 , sr is the unit of solid angle (steradian (dimensionless)), h is Planck's constant (6.62607015×10 -34 J·s), k B is the Boltzmann constant (1.380649×10 -23 J.K. -1 ), c represents the speed of light (299792458 m / s). UV is the minimum value of the distance between the chromaticity point of the emission spectrum on the UV chromaticity diagram and the blackbody radiation locus on the UV chromaticity diagram obtained as described above, and was obtained by optimization. The blackbody radiation temperature of the point of the minimum distance on the blackbody radiation locus is the correlated color temperature T CP The results are shown in Tables 1 to 3. The chromaticity coordinates of Examples 1, 2, 3, 5, 6, 11, 12, 25, and 27 on the xy chromaticity diagram are shown in FIG. 4 together with the chromaticity coordinates of the blackbody locus and the white point.

[0087] In Examples 1 to 29, all of them had the composition range and characteristics of the present invention as shown in Tables 1 to 3, and emitted light extremely close to the blackbody radiation locus on the chromaticity diagram. Furthermore, in Examples 14, 15, and 24, the above-mentioned formula (II) was satisfied, and emitted light even closer to the blackbody radiation locus was obtained.

[0088] (Comparative Examples 1 to 2) A glass composition was obtained in the same manner as in Example 1, except that the glass composition ratio was changed to that shown in Table 4.

[0089] All of the glasses in Comparative Examples 1 and 2 are outside the composition range of the present invention. When these glass samples were irradiated with light from an ultraviolet LED and the emitted light color was visually observed, as shown in Table 4, all of them had a strong yellowish tint, and it was clear that the emitted light had a chromaticity significantly different from that of the blackbody radiation locus.

[0090] [Table 1]

[0091] [Table 2]

[0092] [Table 3]

[0093] [Table 4]

Claims

1. The following components (a), (b) and (c): Component (a): SiO 2 (b) Component; Al 2 O 3 ,and (c) Component; B 2 O 3 , MgO, CaO, SrO and ZrO 2 A component containing at least one selected from the group consisting of Including, Relative to the total amount of the component (a), the component (b) and the component (c), SiO 2 The content is 60 to 73 mol%, A 2 O 3 The content is 10 to 20 mol %, B 2 O 3 The content is 15 mol % or less, The content of MgO is 20 mol % or less, The content of CaO is 20 mol% or less, The content of SrO is 8 mol % or less. ZrO 2 The content ratio of is 2 mol% or less, and The total content of MgO, CaO and SrO is 12 to 25 mol%. and A 2 O 3 and SiO 2 Al relative to the total amount 2 O 3 Molar ratio of (Al 2 O 3 / (Al 2 O 3 +SiO 2 ) is 0.13 to 0.23, R'O and Al 2 O 3 The molar ratio of R'O to the total amount of (R'O / (R'O+Al 2 O 3 ) value, where R'O represents MgO, CaO and SrO) is 0.40 to 0.65; The component (a), the component (b), the component (c), Cu 2 O and SnO 2 Cu relative to the total amount 2 The content of O is 0.1 to 3 mol % and SnO 2 The content of is 1 mol % or less, Cu 2 SnO to O 2 Molar ratio of SnO 2 / Cu 2 O value) is 2.5 or less, It has the property of emitting light at a wavelength of 300 nm or more, The compound represented by the following formula (I) -0.01≦d uv ≦0.01・・・(I) (In formula (I), d uv represents the color difference value calculated based on the point on the UV chromaticity diagram of the emission spectrum obtained by irradiation with ultraviolet light of a wavelength of 365 nm and the blackbody radiation locus. A glass composition comprising:

2. Relative to the total amount of the component (a), the component (b) and the component (c), SiO 2 The content is 62 to 73 mol%, A 2 O 3 The content is 13 to 19 mol%, B 2 O 3 The content is 1 mol% or less, The content of MgO is 11 to 19 mol %, The content of CaO is 6 mol% or less, The content of SrO is 5 mol % or less. and, The total content of MgO, CaO and SrO is 13 to 19 mol%. and The above Al 2 O 3 / (Al 2 O 3 +SiO 2 ) is 0.155 to 0.23; the molar ratio of MgO to R'O (MgO / R'O value) is 0.40 to 1; The above R'O / (R'O+Al 2 O 3 2. The glass composition according to claim 1, wherein the value of .lambda..times ...

3. The following formula (II) -0.005≦d uv ≦0.005・・・(II) (In formula (II), d uv is d in formula (I) uv (Synonymous with The glass composition according to claim 1 or 2, which satisfies the above.

Citation Information

Patent Citations

  • Luminescent glass, light-emitting device equipped with the luminescent glass and manufacturing method of luminescent glass

    JP2014133682A

  • Luminescent glass

    JP2016079045A

  • White light-emitting glass, glass-coated light-emitting element, and light-emitting device

    WO2012063492A1